An empirical note on growth and convergence across Russian regions - Laura Solanko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
This empirical note uses publicly available Goskomstat data to investigate income growth and convergence across Russian regions. Using data for 1992-2001, we find strong sigma divergence simultaneously with beta convergence. he results indicate that per capita income in Russian regions may be converging towards two separate steady states.The poorest regions seem to be converging among themselves, while growth experiences among other regions have been highly heterogeneous.
URN:NBN:fi:bof-201408072013
Keywords: 330; convergence; divergence; Russia; regions; growth